Recurrent Pregnancy Loss Evidence-Based Evaluation, Diagnosis and Treatment - Bashiri, Asher; Harlev, Avi; Agarwal, Ashok (Springer International Publishing : Imprint: Springer, 2016)
Providing the latest evidence-based information on etiology, evaluation and treatment, this unique text provides an in-depth, comprehensive discussion of the epidemiology, genetic and endocrinologic factors and medical and surgical management of recurrent pregnancy loss (RPL). Taking a multidisciplinary approach including psychological treatment and patient perspectives, all aspects of current RPL prevention and treatment are elucidated. Detailed chapters provide real-world illustrative material and cover the set-up and management of RPL clinics and databases, containing practical tips. Recurrent Pregnancy Loss will be an excellent resource for OB-GYN specialists, general and reproductive endocrinologists, radiologists, hematologists, psychiatrists, psychologists, and any other investigators or clinicians treating patients confronted with this emotionally and physically trying condition.